THE CHALLENGES OF RURAL AREAS IN SERBIA PROMISING TOURIST ACTIVITIES - Milenković, Svetislav; Utvić, Svetlana (Economics of Agriculture, 2013)
Challenges of rural areas in Serbia are complex categories, so the work set itself a goal to show how these challenges can help its people interested, which are still developing tourism within the region. In order to prove all, work have to use qualitative and quantitative social science methodology with emphasis on induction, conversion multiplier, surveys in the statistical models. With such methodology, work, has distinct hypotheses: If the rural areas of each country carries a multi-purpose economic dependence, then the rural areas of Serbia must accept tourism as a positive economic challenge, and Tourism in rural areas, if there is a guaranteed capacity of tolerance, must provide rural area to be feedback of its successful economic development. Work, emphasizing challenges of rural areas in tourist activity, has to give results compatible with evidence of field research and indicate directions of tourism development in Serbia rural areas.